The Integrative Strategic Development for Perspective Hotel Enterprise - SKOBKIN, Sergey Sergeevich (Journal of Environmental Management and Tourism, 2019)
The article presents a model for building a strategy based on the principles of structuring strategic goals and their integration to maximize profits and equity based on the growth of competitive advantages. Presented portfolios of strategies to achieve each strategic stage of hotel development. A formula for calculating the cumulative effect of the implementation of the strategy on the basis of cost, income and comparative methods for determining the value of the enterprise is proposed.